Mengelola Watak Dan Potensi Manusia Melalui Weton Dan Neptu Jawa - Ngatipan Ngatipan (Lembaga Pengembangan Kinerja Dosen, 2024)
Javanese culture and society, which has various styles, is characterized by a common identity, both through physical characteristics and other more abstract characteristics. Similarity of identity is physically sensed through the physiognomy produced by a clan/tribe/clan and cultural products. Meanwhile, abstract similarities take the form of views on life, ways of thinking, structure of society, belief systems, and so on. One form of similarity in the way of life and beliefs of the Javanese people can be observed in the paradigm of identifying human character through the weton and neptu approaches. Weton and Neptu are considered and believed to be a way to recognize one's character and potential from something abstract to something relatively more concrete. In the Javanese belief system, character and potential are two things that determine the development of culture and the success of life of the Javanese people themselves. So, empirically weton and neptu are a way of life that must be taken in order to be happy and prosperous.